2021
DOI: 10.1016/j.jcot.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and safety of intra-articular injection of HYALGO in the management of knee osteoarthritis symptoms: A multicenter prospective study

Abstract: Background: The reduced concentration of hyaluronic acid in the synovial fluid, leading to impairment of joint function and painful symptomatology during knee osteoarthritis (OA), can be restored by using injectable formulations of hyaluronic acid (HA) and chondroitin sulfate (CS), variable for relative composition, HA/CS molecular modifications, and injection protocols. The present study aims to assess the safety and performance of the intra-articular (IA) viscosupplementing agent HYALGO, a formulation combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…To date, almost all the CS used either as food ingredients or as pharma-active molecules and as macromolecules in solution/combination with HA are of animal extractive origin [20,21,[27][28][29]. In this respect, as previously discussed, the commercialized CS are very heterogeneous molecules.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, almost all the CS used either as food ingredients or as pharma-active molecules and as macromolecules in solution/combination with HA are of animal extractive origin [20,21,[27][28][29]. In this respect, as previously discussed, the commercialized CS are very heterogeneous molecules.…”
Section: Discussionmentioning
confidence: 98%
“…The authors reported that the proposed intervention was able to assure pain relief and improved function over 6 months of follow-up [28]. Interestingly, the combined intra-articular injection of HA and CS was effective since the first application, probably due to an anti-inflammatory effect [29]. More interesting, a novel biofermentative unsulfated chondroitin has been obtained at a high purity grade by biotechnological inventive processes and reported a molecular weight like those of fish (shark fins) extractive chondroitin sulfate, this one being the larger molecules among extractive CS.…”
Section: Introductionmentioning
confidence: 99%
“…This study concluded that three injections of HYALGO were safe and effective to manage symptomatic knee OA, with a beneficial effect that increased progressively over time, peaking 6 months after injection. [ 69 ] The histological changes in knee cartilage and bone following the administration of two different CS products in two experimental OA models (MIA) in rats were studied ( Figure ). It was found that high‐quality pharmaceutical‐grade CS ensures optimal efficacy and safety of the final product in patients with OA.…”
Section: Biomaterials and Viscosupplement‐based Therapiesmentioning
confidence: 99%